The Enantiomeric Separation of Tetrahydrobenzimidazoles Cyclodextrins‐ and Cyclofructans. Issue 2 (13th December 2012) - Perera, Sirantha; Na, Yun‐Cheol; Doundoulakis, Thomas; Ngo, Victor J.; Feng, Qing; Breitbach, Zachary S.; Lovely, Carl J.; Armstrong, Daniel W.
ABSTRACT High performance liquid chromatography (HPLC) and capillary electrophoresis (CE) were used to examine the enantiomeric separation of a series of 17 racemic tetrahydrobenzimidazole analytes. These compounds were prepared as part of a synthetic program directed towards a select group of pyrrole‐imidazole alkaloids. This group of natural products has a unique framework of pyrrole‐ and guanidine‐containing fused rings which can be constructed through the intermediacy of a tetrahydrobenzimidazole scaffold. Several bonded cyclodextrin‐ (both native and derivatized) and derivatized cyclofructan‐based chiral stationary phases were evaluated for their ability to separate these racemates via HPLC. Similarly, several cyclodextrin derivatives and derivatized cyclofructan were evaluated for their ability to separate this set of chiral compounds via CE. Enantiomeric selectivity was observed for the entire set of racemic compounds using HPLC with resolution values up to 3.0. Among the 12 different CSPs, enantiomeric recognition was most frequently observed with the Cyclobond RN and LARIHC CF6‐P, while the Cyclobond DMP yielded the greatest number of baseline separations. Fifteen of the analytes showed enantiomeric recognition in CE with resolution values as high as 5.0 and hydroxypropyl‐γ‐cyclodextrin was the most effective chiral additive. Chirality 25:133–140, 2013. © 2012 Wiley Periodicals, Inc.